Videos summarizing evidence-based messages on nutritional benefits of biofortified foods and relevance to national food programs in India - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Two videos are publicly available on YouTube. The short version is 2 minutes and the longer one is 4 minutes. They summarize key messages from the recently completed HarvestPlus-Cornell Multiple Biofortified Crop Efficacy Study in rural Madanapalle.